Blockchain Technology Integration for Enhancing Security and Reliability in Modern Information Systems - Septyawati, Diana; Suroso, Suroso; Bhupathiraju, Sivakumarraju; Toh Hua, Chua; Fitriani, Anandha (Pandawan Sejahtera Indonesia, 2025)
Blockchain has become a critical digital infrastructure for strengthening data integrity, transparency, and trust within intelligent information systems, particularly in environments that depend on continuous AI–IoT data exchange. Despite its potential, empirical evidence quantifying blockchain’s actual security benefits remains limited. This study employs a hybrid analytical design combining Smart Partial Least Squares (SmartPLS) modeling with expert-based qualitative triangulation. Five core constructs Resistance to Attack, Data Integrity, Transparency, System Security, and User Satisfaction and Trust were evaluated to capture both the technical and perceptual dimensions of blockchain-enabled security. The research aims to empirically determine how blockchain architecture enhances intelligent information security and to identify the structural relationships among its socio technical components. Quantitative findings reveal that blockchain improves data integrity by 23%, increases transaction transparency by 19%, and enhances user trust by 17% compared with centralized systems. The model demonstrates strong reliability (ρc > 0.85) and high explanatorypower (R2 > 0.70), confirming the robustness of the proposed framework. The study advances theoretical understanding by validating blockchain as a socio technical enabler of secure and trustworthy intelligent ecosystems. Practically, the findings highlight how decentralization promotes ethical, resilient, and transparent digital infrastructures capable of supporting next generation intelligentsystems.